(untitled) (INTERNATIONAL SEMINAR, 2025)
The development of digital technology has driven the increasingly widespread distribution of digital products and content, ranging from applications, software, music, films, and other virtual products. This situation has given rise to various new challenges in consumer protection, particularly regarding the authenticity, quality, data security, and legality of digital products. Intellectual Property Rights (IPR) play a crucial role in ensuring that consumers obtain legal, safe, and standard-compliant digital products. This article analyzes the relationship between IPR and consumer protection, focusing on how IPR enforcement can prevent the spread of illegal digital products, piracy, and unlicensed content that has the potential to harm consumers. The method used is a literature study with a descriptive qualitative approach, through a review of literature from the last 2–5 years, statutory provisions, and empirical reports on IPR violations in Indonesia. The results of the study indicate that the rise of pirated digital content, modified applications, and counterfeit digital goods on online platforms occurs due to weak supervision, low consumer digital literacy, and limited law enforcement. To improve consumer protection, strengthening technology-based regulations, increasing IPR literacy, optimizing digital platform oversight, and collaboration between the government, industry players, and the public are needed. This effort is expected to create a safer, fairer digital ecosystem, providing legal certainty for both consumers and rights holders.